A subset analysis of a phase II trial evaluating the use of DFMO as maintenance therapy for high‐risk neuroblastoma. Issue 11 (24th May 2020) - Lewis, Elizabeth C.; Kraveka, Jacqueline M.; Ferguson, William; Eslin, Don; Brown, Valerie I.; Bergendahl, Genevieve; Roberts, William; Wada, Randal K.; Oesterheld, Javier; Mitchell, Deanna; Foley, Jessica; Zage, Peter; et al.
Abstract: Neuroblastoma is a sympathetic nervous system tumor, primarily presenting in children under 6 years of age. The long‐term prognosis for patients with high‐risk neuroblastoma (HRNB) remains poor despite aggressive multimodal therapy. This report provides an update to a phase II trial evaluating DFMO as maintenance therapy in HRNB. Event‐free survival (EFS) and overall survival (OS) of 81 subjects with HRNB treated with standard COG induction, consolidation and immunotherapy followed by 2 years of DFMO on the NMTRC003/003b Phase II trial were compared to a historical cohort of 76 HRNB patients treated at Beat Childhood Cancer Research Consortium (BCC) hospitals who were disease‐free after completion of standard upfront therapy and did not receive DFMO. The 2‐ and 5‐year EFS were 86.4% [95% confidence interval (CI) 79.3%‐94.2%] and 85.2% [77.8%‐93.3%] for the NMTRC003/003b subset vs 78.3% [69.5%‐88.3%] and 65.6% [55.5%‐77.5%] for the historical control group. The 2‐ and 5‐year OS were 98.8% [96.4‐100%] and 95.1% [90.5%‐99.9%] vs 94.4% [89.3%‐99.9%] and 81.6% [73.0%‐91.2%], respectively. DFMO maintenance for HRNB after completion of standard of care therapy was associated with improved EFS and OS relative to historical controls treated at the same institutions. These results support additional investigations into the potential role of DFMO in preventing relapse in HRNB. Abstract : What's new? The long‐term prognosis for patients with high‐risk neuroblastoma (HRNB) remains poor despite aggressive multimodal therapy. This phase II clinical trial update is the first study to demonstrate statistically and clinically significant improvement in event‐free and overall survival in HRNB patients as a result of DFMO administration following standard upfront therapy relative to a closely matched historical control. The findings support DFMO maintenance as a novel strategy to prevent relapse in a high‐risk population for relapse following frontline treatment.